DO-SRS imaging of metabolic dynamics in aging Drosophila. Issue 24 (15th November 2021) - Li, Yajuan; Zhang, Wenxu; Fung, Anthony A.; Shi, Lingyan
Abstract : Emerging studies have shown that lipid metabolism plays an important role in aging. Abstract : Emerging studies have shown that lipid metabolism plays an important role in aging. High resolution in situ imaging of lipid metabolic dynamics inside cells and tissues affords a novel and potent approach for understanding many biological processes such as aging. Here we established a new optical imaging platform that combines D2 O-probed stimulated Raman scattering (DO-SRS) imaging microscopy and a Drosophila model to directly visualize metabolic activities in situ during aging. The sub-cellular spatial distribution of de novo lipogenesis in the fat body was quantitatively imaged and examined. We discovered a dramatic decrease in lipid turnover in 35-day-old flies. Decreases in protein turnover occurred earlier than lipids (25-day vs. 35-day), and there are many proteins localized on the cell and lipid droplet membrane. This suggests that protein metabolism may act as a prerequisite for lipid metabolism during aging. This alteration of maintenance of protein turnover indicates disrupted lipid metabolism. We further found a significantly higher lipid turnover rate in large LDs, indicating more active metabolism in large LDs, suggesting that large and small LDs play different roles in metabolism to maintain cellular homeostasis. This is the first study that directly visualizes spatiotemporal alterations of lipid (and protein) metabolism in Drosophila during the aging process. Our study not only demonstrates a new imaging platform for studying lipid metabolism, but also unravels the important interconnections between lipid metabolism and aging.